OPTIMALISASI HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA WORDWALL PADA SISWA KELAS V SDN 01 KANIGORO - Windiana Lailatul Fitria; Fauziyah Hasna Saputri; Novita Kurnia Syafitri; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the mathematics learning outcomes of fifth-grade students at SDN 01 Kanigoro through the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media. The background of the study is the low student performance in the topic of plane figures, which is attributed to the dominance of lecture-based teaching methods and the lack of engaging learning media. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of the study were 10 fifth-grade students. Data were collected using tests, observations, interviews, and documentation. The results showed an improvement in student learning outcomes: from a pre-cycle average score of 57.1 with 0% mastery, to 67.9 with 30% mastery in the first cycle, and significantly increased to an average score of 81.6 with 90% mastery in the second cycle. The implementation of the TGT model assisted by Wordwall proved effective in creating an interactive, enjoyable, and competitive learning atmosphere, which successfully enhanced students’ motivation and academic achievement.